Clinical use of tumor biomarkers in prediction for prognosis and chemotherapeutic effect in esophageal squamous cell carcinoma - Yang, Yuchong (BMC Cancer, 2019)
BACKGROUND: Growing evidence has indicated that tumor biomarkers, including cytokeratin 19 fragment antigen 21–1 (Cyfra21–1), carbohydrate antigen 19–9 (CA19–9), carbohydrate antigen 72–4 (CA72–4), carcinoembryonic antigen (CEA) and squamous cell carcinoma antigen (SCC-Ag) were reported to be commonly used in diagnosis and prognosis in esophageal squamous cell carcinoma (ESCC). However, which is the best marker for predicting prognosis remains unknown. Few papers focused on the relationship between tumor biomarkers and postoperative treatment in ESCC. METHODS: A total of 416 ESCC patients were enrolled in this study. The association between tumor markers and overall survival (OS) was analyzed using Kaplan-Meier method with log-rank test, followed by multivariate Cox regression models. RESULTS: The results of Cox multivariate analysis indicated that among these tumor biomarkers, CA19–9 (≥ 37 vs. < 37) [hazard ratio (HR) = 2.130, 95% confidence interval (CI) = 1.138–3.986, p = 0.018] and CEA (≥ 5 vs. < 5) (HR = 1.827, 95% CI = 1.089–3.064, p = 0.022) were the independent prognostic factors of poor OS. For the ESCC patients with CA19–9 < 37, CEA < 5 or SCC-Ag < 1.5, the surgery plus postoperative chemotherapy group had a significantly longer OS than the surgery group alone (p < 0.05), but this significant difference of OS between these two groups cannot be found in patients with CA19–9 ≥ 37, CEA ≥ 5 or SCC-Ag ≥ 1.5 (p > 0.05). CONCLUSIONS: CEA and CA19–9 maybe are superior to other tumor biomarkers as prognostic indicators in ESCC. CA19–9, CEA, SCC-Ag may be useful in predicting the therapeutic effect of postoperative chemotherapy in ESCC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5755-5) contains supplementary material, which is available to authorized users.